Viral etiology of prostate cancer: Genetic alterations and immune response. A literature review. (April 2018) - Abidi, Syed Hani; Bilwani, Fareena; Ghias, Kulsoom; Abbas, Farhat
Abstract: Prostate cancer is one of the most common cancers in men. Recent estimates suggest that over a million men are diagnosed with the disease annually. Prostate cancer pathogenesis involves both heritable and environmental factors. The molecular events involved in the development or progression of prostate cancer are still unclear. Recent body of literature highlights the role of viral infections in initiation or progression of prostate cancer. In this regard, certain viruses have been reported to interact with host proteins and bring about changes in genetic, immunological and inflammatory events that lead to initiation or progression of prostate cancer. We conducted a comprehensive PubMed database search to identify publications relevant to viruses associated with prostate cancer. In this review, we discuss the possible viral etiology of prostate cancer and evidence of viral-mediated genetic changes, and immune dysregulation involved in initiation or progression of prostate cancer. Highlights: Prostate cancer (PCa) pathogenesis involves both heritable and environmental factors. The molecular events involved in the development or progression of prostate cancer are still unclear. Here we discuss viral etiology of PCa and evidence of viral-mediated genetic changes, and immune dysregulation in PCa.